MOTIVASI KUNJUNGAN WISATAWAN PADA OBJEK WISATA BLUE LAGOON DI YOGYAKARTA - Ashfia Durrunafis; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Motivation is the impetus, driving force or force that causes a person to take an action or deed to achieve a goal. This study aims to find out what are the motivations for visiting tourists in the Blue Lagoon Tourist Attraction, D.I Yogyakarta. In this study, researchers used qualitative research methods. Researchers collected data by means of observation, interviews and documentation. The data analysis technique in this study uses the Miles and Huberman model which includes the process of data reduction, data presentation and ends with drawing conclusions. The subjects in this study included 10 informants who were tourists in the Blue Lagoon Tourist Attraction. Tourist motivation which was studied in this study was collected into 4 sub-variables namely physical motivation, cultural motivation, interpersonal motivation and status and prestige motivation, McIntosh and Goeldner (1995) in I Made Sendra, et al (2019). With indicators of refreshing body and mind, maintaining health, exercising with family, having fun, wanting to relax from daily routines, learning customs, knowing traditions, studying culture, seeing art, meeting new people, strengthening relationships with friends/relatives, seek new and different experiences, share hobbies, follow new travel trends, gain knowledge of new tourism activities, learn new skills, increase satisfaction for carrying out tourism trends. The results of the research that has been done regarding the motivation of the visit, tourists visit the Blue Lagoon Tourism Village with the aim of enjoying physical motivation where tourists can enjoy some physical activities that can provide relaxation and comfort. Keywords: motivation, tourist motivation, Blue Lagoon Tourist Attraction